Development of Chitosan and NanoDot (CNDs) as chemosensors for contact oil damage detection at magnetic fields on electric currents in solar cells - Ridwan Arrasyid; Indri Dayana; Habib Satria; Moranain Mungkin (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2023)
This research aims to see development of chitosan and nanodot as chemosensor for contact oil damage at magnetic fields on electric current in solar cell based on the results of 20 experiments. It can be concluded that for each equal increase in the magnetic field on a straight wire, the result is 0.25 T. For every constant increase in the strength of the electric current in the solar panel, the magnetic field also increases15 . The same data is obtained for the magnetic field of straight wire and circular wire because the magnitude of phi is neglected, because only phi is the differentiator.The greater the magnetic field, the greater the electric current in the solar cell and vice versa. This relationship is a straight line (linear)